PERTIMBANGAN HAKIM DALAM MENGABULKAN KASASI SENGKETA MEREK PADA PERKARA NOMOR 332 K/Pdt.Sus- HKI/2021 - Bretna Shiwe Benaya Uneputty; Arsyad Aldyan (Verstek, 2026)
This article examines the analysis of the Supreme Court Judge's consideration in granting the cassation of PT Unilever Indonesia, Tbk against Hardwood Private Limited in the “STRONG” toothpaste brand dispute. This article shows that at the first level, the Central Jakarta Commercial Court granted Hardwood Private Limited's lawsuit with the consideration that the “Strong” trademark had been registered first, so it was entitled to legal protection based on the “first to file” principle. However, at the cassation level, the Supreme Court overturned the decision on the grounds that the word “STRONG” in the Defendant's “PEPSODENT STRONG 12 JAM” mark was not substantially similar to the Plaintiff's mark. The Supreme Court judges argued that the word “STRONG” is a common adverb and is not a dominant element in the mark. There is an inconsistency in the application of the “first to file” principle in the settlement of trademark disputes in the Cassation Decision. This case shows that even though a trademark has been registered first, it does not automatically get legal protection if it cannot be proven that there is a similarity in essence with the disputed trademark.